LSD worldpeace - Roberts, Joe 1976- (Anthology Editions, 2023)
The paintings, drawings, and mixed-media works of Joe Roberts are transportive in the cosmic sense. Through their intuitive blend of styles and subjects, they serve as portals into a welcomingly hallucinatory world: a place where gleeful mashups of childhood signifiers (comic book detritus, cartoon mascots) exist cozily alongside countercultural reference points (ouija boards, sci-fi paperbacks, UFOs) and earnest flashes of the personal (diaristic sketches, confessional trip reports). Reissued for the first time since 2015, LSD Worldpeace documents the extraordinary creativity and scrappy methods of Roberts’s early career, replete with collages, action figures, and dioramas, in addition to the paintings for which he’s become so celebrated. With introductory texts by Myla DalBesio and Matthew Ronay, LSD Worldpeace is the product of a wildly imaginative artist moving freely between modes, guided by a boundless vision
Impressum: Originally published in 2014 by Unpiano Books
Keywords: Roberts, Joe -- 1976-; Roberts, Joe; Bildband